2003
DOI: 10.1097/01.smj.0000056661.42816.74
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Incidence of Pancreatitis in Patients Undergoing Sphincter of Oddi Manometry: A Successful Quality Improvement Project

Abstract: By adopting a protocol to perform diagnostic SOM, separate from ERCP and sphincterotomy, we were able to decrease the incidence of pancreatitis considerably at our institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Employing a triple-lumen catheter with three side holes located 2 mm apart, Toouli et al [11] demonstrated that 55–60% of the SO phasic waves exhibited downward propagation, and proposed manometric criteria for the diagnosis of SO dysfunction (table 1). Aspiration of one of the triple lumens and separate performance of manometry and sphincterotomy were reported to be effective to reduce a relatively high incidence of acute pancreatitis as a complication of manometry [12]. A remarkable recent advance is the development of a ‘sleeve’ catheter which can be retained within the human SO and thus allows for prolonged SO manometry [13].…”
Section: So Function Testsmentioning
confidence: 99%
“…Employing a triple-lumen catheter with three side holes located 2 mm apart, Toouli et al [11] demonstrated that 55–60% of the SO phasic waves exhibited downward propagation, and proposed manometric criteria for the diagnosis of SO dysfunction (table 1). Aspiration of one of the triple lumens and separate performance of manometry and sphincterotomy were reported to be effective to reduce a relatively high incidence of acute pancreatitis as a complication of manometry [12]. A remarkable recent advance is the development of a ‘sleeve’ catheter which can be retained within the human SO and thus allows for prolonged SO manometry [13].…”
Section: So Function Testsmentioning
confidence: 99%
“…Bin-Sagheer et al [47] hypothesized that carrying out sphincter of Oddi manometry (SOM) without ERCP at the same time might reduce the rate of postprocedural pancreatitis in comparison with an approach in which the two methods were carried out concomitantly. Pancreatitis developed in three of 41 patients after SOM alone (7.3 %), and in one of five patients who subsequently underwent ERCP with sphincterotomy.…”
Section: State Of the Art Reviewmentioning
confidence: 99%
“…9 Among patients who undergo ERCP, the specific procedural intervention may vary widely, including biliary sphincterotomy, pancreatic sphincterotomy, pancreatic stent placement, manometry, and minor papilla therapy for divisum depending on the clinical context, local practice, and physicians' preference. [10][11][12][13][14][15][16][17][18] These more invasive strategies may follow an extensive diagnostic evaluation with laboratory testing, imaging with computed tomography and/or magnetic resonance imaging or cholangiopancreatography with or without secretin enhancement, endoscopic ultrasound (EUS), and Sphincter of Oddi manometry. 13 In the setting of RAP, it is unclear which patients are being referred for ERCP.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] These more invasive strategies may follow an extensive diagnostic evaluation with laboratory testing, imaging with computed tomography and/or magnetic resonance imaging or cholangiopancreatography with or without secretin enhancement, endoscopic ultrasound (EUS), and Sphincter of Oddi manometry. 13 In the setting of RAP, it is unclear which patients are being referred for ERCP. In patients who undergo ERCP, it is unclear which interventions are being performed.…”
Section: Introductionmentioning
confidence: 99%